Ruptured Mitral Annular Abscess with Severe Mitral Regurgitation in a Child - Thapa, Bhuwan; Pandey, Naveen Kumar; Mandal, Subhash Chandra; Sapkota, Ramesh (Nepal Mediciti Medical Journal, 2025)
Infective endocarditis (IE) in children is rare but can present with devastating complications. Staphylococcus aureus is an aggressive pathogen that can lead to valvular destruction, annular abscess formation, and rupture, resulting in severe mitral regurgitation and hemodynamic compromise. We report the case of a 14-year-old child from a remote village in Eastern Nepal, who presented with pleuritic chest pain for 2 days, progressive dyspnea (NYHA I-IV) for 7 days, and persistent fever for 15 days. The patient had undergone incision and drainage for a Staphylococcus aureus thigh abscess 10 days earlier and had been on empirical antibiotics since then. On examination, he was tachypneic, tachycardic, and maintaining oxygen saturation with 4L/min via nasal prongs. A high-pitched, grade V/VI systolic murmur was heard over the apex, radiating to the axilla, along with a pericardial rub. Blood cultures were sterile, likely due to prolonged antibiotic use. ECG showed sinus tachycardia with ST elevation and PR depression in all leads except aVR, suggestive of pericarditis. Chest X-ray was normal. Transthoracic echocardiography (TTE) revealed severe mitral regurgitation with a ruptured abscess cavity involving the posterior mitral leaflet and annulus, fistulating into the left atrium. This case highlights the aggressive nature of Staphylococcus aureus infections, leading to annular abscess formation and rupture in a previously healthy child. Early suspicion, prompt echocardiographic assessment, and surgical intervention are crucial for survival. Prolonged empirical antibiotic use may obscure microbiological diagnosis, delaying definitive treatment.